The Associations of Plant Protein Intake With All-Cause Mortality in CKD - Chen, Xiaorui; Wei, Guo; Jalili, Thunder; Metos, Julie; Giri, Ajay; Cho, Monique E.; Boucher, Robert; Greene, Tom; Beddhu, Srinivasan (American journal of kidney diseases, 2016)
Plant protein intake is associated with lower production of uremic toxins and lower serum phosphorus levels. Therefore, at a given total protein intake, a higher proportion of dietary protein from plant sources might be associated with lower mortality in chronic kidney disease. Observational study. 14,866 NHANES III participants 20 years or older without missing data for plant and animal protein intake and mortality. Plant protein to total protein ratio and total plant protein intake. Patients were stratified by estimated glomerular filtration rate (eGFR)<60 or ≥60mL/min/1.73m2. All-cause mortality. Plant and total protein intakes were estimated from 24-hour dietary recalls. Mortality was ascertained by probabilistic linkage with National Death Index records through December 31, 2000. Mean values for plant protein intake and plant protein to total protein ratio were 24.6±13.2 (SD) g/d and 33.0% ± 14.0%, respectively. The prevalence of eGFRs<60mL/min/1.73m2 was 4.9%. There were 2,163 deaths over an average follow-up of 8.4 years. Adjusted for demographics, smoking, alcohol use, comorbid conditions, body mass index, calorie and total protein intake, and physical inactivity, each 33% increase in plant protein to total protein ratio was not associated with mortality (HR, 0.88; 95% CI, 0.74-1.04) in the eGFR≥60mL/min/1.73m2 subpopulation, but was associated with lower mortality risk (HR, 0.77; 95% CI, 0.61-0.96) in the eGFR<60mL/min/1.73m2 subpopulation. In sensitivity analyses, results were similar in those with eGFR<60mL/min/1.73m2 defined by serum cystatin C level. Whether results are related to plant protein itself or to other factors associated with more plant-based diets is difficult to establish. A diet with a higher proportion of protein from plant sources is associated with lower mortality in those with eGFR<60mL/min/1.73m2. Future studies are warranted to determine the causal role of plant protein intake in reducing mortality in those with eGFR<60mL/min/1.73m2.